Application of Level Set Method for Shape and Topology Optimization in an Electromagnetic System - Sun Kim, Young; Yoon Lee, Dong (International Journal of Engineering and Technology, 2018)
Level set methods(LSM) are conceptual methods for using level sets as tools for numerical analysis of surfaces and geometries. The advantage of the level set model is that you can perform numerical calculations involving curves and surfaces in a fixed grid without parameterizing these objects. In recent years, it has been applied to structural design optimization of mechanical engineering, and it has been actively studied as a new design technique overcoming the problems of existing shape sensitivity analysis method and phase optimization method. You can also use the level setting method to easily follow how the topology changes. In this study, we show the application of the level set method to the optimal design using sensitivity analysis. This paper presents applications of dielectric electrode design, moving objects and particle dynamics in magnetic field systems.Â Â